2018
DOI: 10.1186/s11658-018-0115-z
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin-LR regulates circadian clock and antioxidant gene expression in cultured rat cardiomyocytes

Abstract: BackgroundMicrocystins are waterborne environmental toxins that induce oxidative stress and cause injuries in the heart. On the other hand, many physiological processes, including antioxidant defense, are under precise control by the mammalian circadian clock.ResultsIn the present study, we evaluated the effect of microcystin-LR (MC-LR) on the rhythmic expression patterns of circadian and antioxidant genes in rat cardiomyocytes using the serum shock technique. We found that a non-toxic dose (10 μm) of MC-LR de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…To date, a large number of studies have shown that MCs can induce cardiovascular toxicity in vivo and vitro directly [36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53]. Table 1 and Table 2 represent summaries of cardiovascular toxicity in in vivo and vitro studies, respectively.…”
Section: Cardiovascular Toxicity Of Mcsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, a large number of studies have shown that MCs can induce cardiovascular toxicity in vivo and vitro directly [36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53]. Table 1 and Table 2 represent summaries of cardiovascular toxicity in in vivo and vitro studies, respectively.…”
Section: Cardiovascular Toxicity Of Mcsmentioning
confidence: 99%
“…In addition, MC-LR has recently been confirmed to inhibit the heart rate of Japanese Medaka (Oryzias Latipes) [44]. Currently, Xu et al [49] provided an explanation of the possible role of antioxidant enzymes in the toxicological mechanisms of MCs at the transcription level by treating H 9 C 2 (a kind of rat cardiomyocyte) cell lines with 10 μM MC-LR. The expression levels of cardiac rhythm and antioxidant genes were detected and the results suggested that the expression levels of rhythmic genes ( baml1, cry1, cry2, per1, per2 ) were inhibited, while the antioxidant genes ( catalase, ho-1, sod1, sod2 ) were upregulated.…”
Section: Cardiovascular Toxicity Of Mcsmentioning
confidence: 99%